Relacja człowiek-zwierzę w poemacie "Cynegetica" Faliskusa na marginesie tradycji antycznych polowań - Gryksa-Pająk, Edyta (Colloquia Litteraria, 2024)
The aim of this article is to describe the relations between man and animals (man and horse and man and dog) in antiquity. Particular emphasis will be placed on the care given to animals involved in hunting. It was described by Grattius Faliscus in his poem entitled Cynegetica, which is a valuable collection of advice and interesting facts about ancient hunting expeditions.